A Real-Time, Distributed and Context-Aware System for Managing Solidarity Campaigns - Alves, Ana OLIVEIRA; Dias, Tiago; Silva, David (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2015)
We present a project implemented on the field which has two separate strands, one refers on collecting crowd sensing data through mobile apps where context is (near) automatically induced, another is related to a practical application of this method in a real time system to manage solidarity campaigns in collecting goods. Here, we cover both parts, we applied an experimental setup and obtained results and insights in a third sector institution, Caritas Diocesana of Coimbra[1], a non-profit organization part of Caritas[2]. As main contribution, we propose a distributed architecture for Mobile Crowd Sensing able not only to allow real time inventory through simultaneous campaigns but also it gives feedback to volunteers in order to instantly acquire information about which categories of goods are more needed [1] http://www.caritas.pt/site/nacional/ Portuguese Website (last visited in October 2015) [2] http://www.caritas.eu/ (last visited in October 2015)